Critical Analysis of the Production of Western Knowledge and Its Implications for Indigenous Knowledge and Decolonization - Francis Akena, Adyanga (Journal of Black Studies, 2019)
There has been a persistent contest among contemporary scholars over what is considered legitimate knowledge. This contest has implications on ways of knowing, organizing society, and responding to environmental challenges. The Western education system is a hybrid of different knowledge, adopted through European global expansion, to enrich our learning in formal educational settings. This article examines the production of Western knowledge and its validation, imposition, and effects on indigenous people and their knowledge. The author argues that there is a relationship between knowledge producers and their motives with the society in which they live. This relationship influences what is considered “legitimate knowledge” in society, politics, and economy in non-Western contexts.